AKMESYNERGETIC PRINCIPLES OF FORECASTING THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF SOCIO-ECONOMIC SPECIALISTS - Гладкова, Валентина (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article analyzes the akmesinergic principles of forecasting the development of professional competence of socionomic specialists. Important professional competencies are identified that will contribute to the provision of high-quality qualified assistance by socionomic specialists to people who really need it. These are: sociability, creativity, responsibility, analytical thinking, empathy, leadership qualities, the ability to solve strategic and tactical problems, perseverance, anticipation. In personal and professional life, the ability to predict the consequences of one’s actions, to engage in personal and professional self-forecasting with subsequent self-realization is very important. The purpose of the article is to determine and analyze the akmesinergic principles of forecasting the development of professional competence of socionomic specialists. Research methods: analysis and synthesis, comparison and generalization, deduction and scientific induction, abstraction and modeling. Results: The latest methodological approaches and principles that constitute the theoretical basis of the study are analyzed. Among the methodological approaches, complex, systemic, subjective, activity, cultural, personal, synergistic, acmeological are identified. Attention is focused on the importance of the acme-synergetic approach, which was formed within the framework of fundamental acmeology (in particular, its component - synergistic acmeology). A number of methodological principles are analyzed, namely: system-structural, determinism, development, humanism, subjectivity, life activity, vertex, invariance. The correlation between the professionalism of a socio-economic profile specialist and his professional competence, the stage of development of this competence is considered. The structure of acme-synergetic self-improvement (self-development) is analyzed, which involves four processes: self-determination, self-prediction, self-training and self-realization. The essence of forecasting (acmefutureing) and the evolution of the concept of "adaptive acmefutureing" are analyzed in detail: acmefutureing, habilitation acmefutureing, synergistic professional acmefutureing, adaptive acmefutureing. Discussion: The process of professional self-development/self-improvement of a socio-economic profile specialist is influenced by the extra-environment and intra-environment. The process of professional self-development (self-improvement) itself takes place in the meso-environment. In the process of forecasting the development of professional competence of a socio-economic profile specialist, it is advisable to model the trajectory of such development and develop its author’s program. Key words: acme-synergetic approach; acmefutureing; methodological principles; forecasting; professional competence; self-development; self-improvement; socio-economic profile specialist.